1992
DOI: 10.1111/j.1476-5381.1992.tb14495.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of non‐adrenergic non‐cholinergic inhibitory neurotransmission in rat gastric fundus by the α2‐adrenoceptor agonist, UK‐14,304

Abstract: 1 The influence of the X2-adrenoceptor agonist, UK-14,304, on non-adrenergic non-cholinergic (NANC) relaxation induced by electrical field stimulation was investigated in longitudinal muscle strips of the gastric fundus of reserpinized rats.2 In tissues where tone was raised by 3 x l0' M prostaglandin F2, (PGF2.), the inhibitory effect of 10-6 M UK-14,304, on the NANC relaxations induced by short train stimulation (40 V, I ms, 20 s) was inversely related to the stimulus frequency (1-4-16 Hz). UK-14,304 (10-6 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Prejunctional modulation of NANC neurotransmission in the gastrointestinal tract was previously decribed in only a few tissues (see Introduction); in the rat gastric fundus (Mac-Donald et al, 1990) and the guinea-pig proximal colon (Kojima et al, 1988), the prejunctional inhibition of the NANC relaxations was reported to be mediated by (X2adrenoceptors. Recently Lefebvre & Smits (1992) showed in the rat gastric fundus that UK-14,304 blocked the NANC relaxations induced by short train stimulation, previously demonstrated to be mediated by NO (Li & Rand, 1990;Boeckxstaens et al, 1991a), suggesting prejunctional inhibition of NO release via M2-adrenoceptor activation. In contrast to our results, clonidine did not affect the NANC relaxations in the rat gastric fundus.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Prejunctional modulation of NANC neurotransmission in the gastrointestinal tract was previously decribed in only a few tissues (see Introduction); in the rat gastric fundus (Mac-Donald et al, 1990) and the guinea-pig proximal colon (Kojima et al, 1988), the prejunctional inhibition of the NANC relaxations was reported to be mediated by (X2adrenoceptors. Recently Lefebvre & Smits (1992) showed in the rat gastric fundus that UK-14,304 blocked the NANC relaxations induced by short train stimulation, previously demonstrated to be mediated by NO (Li & Rand, 1990;Boeckxstaens et al, 1991a), suggesting prejunctional inhibition of NO release via M2-adrenoceptor activation. In contrast to our results, clonidine did not affect the NANC relaxations in the rat gastric fundus.…”
Section: Discussionmentioning
confidence: 93%
“…Recently Lefebvre & Smits (1992) Lefebvre, 1988), complicating the study of prejunctional regulation of NO release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PACAP638 also significantly inhibited the ij.ps. (Grider et al, 1985), rat (Li & Rand, 1990;Lefebvre & Smits, 1992) and pig (Lefebvre et al, 1995) gastric fundus, the rabbit (Biancani et al, 1985) and opossum (Goyal et al, 1980;Nurko & Rattan, 1988) lower oesophageal sphincter, and the chicken rectum (Komori & Ohashi, 1990). Charybdotoxin has also been reported to inhibit nitric oxide-independent relaxation in rabbit abdominal aorta and carotid artery (Cowan et al, 1993), and to inhibit partly the nitric oxide-induced relaxation in rabbit aortic smooth muscle cells (Bolotina et al, 1994).…”
Section: Discussionmentioning
confidence: 99%